Ethnomathematics as a Pillar of Ethnopedagogy in STEM: A Case Study of Mathematics Education Students’ Critical Understanding - Atmaja, I Made Dharma; Puspadewi, Kadek Rahayu; Payadnya, I Putu Ade Andre (Jurnal Pendidikan Progresif, 2025)
Ethnomathematics as a Pillar of Ethnopedagogy in STEM: A Case Study of Mathematics Education Students’ Critical Understanding. Objectives: This research aims to analyze students' critical understanding of the role of ethnomathematics as a fundamental pillar of ethnopedagogy, particularly in the context of Science, Technology, Engineering, and Mathematics (STEM) education. Specifically, this analysis focuses on dissecting the structural components and argumentation patterns that constitute students' conceptual framework. Methods: This research used a descriptive qualitative approach. Primary data consisted of five sets of written arguments from students in the mathematics education program who had completed the ethnomathematics course. The study involved five undergraduate students as the primary participants. This textual data was analyzed using thematic analysis to identify, examine, and report systematically emerging patterns of understanding. Findings: This analysis shows that students develop structured patterns of understanding. First, they position ethnomathematics as the philosophical foundation for ethnopedagogy by rejecting the assumption of universalism in science and mathematics. This perspective goes beyond mere cultural appreciation, framing ethnomathematics as a decolonizing force that challenges the hegemony of Western knowledge systems. Second, they identify ethnomathematics as the primary pedagogical mechanism for contextualising STEM, serving to address students' alienation from abstract subject matter. Third, they validate local wisdom as an authentic source of STEM content, recognizing cultural practices as valid scientific knowledge. Uniquely, students conceptualize this not as supplementary content, but as the core epistemic bridge that unifies the separate disciplines of STEM within a single cultural activity. Conclusion: The data indicate that students in mathematics education conceptualize ethnomathematics as a central element for the effective implementation of ethnopedagogy in STEM education. This implies that students have successfully internalized a transformative pedagogical framework, viewing indigenous knowledge not as peripheral but as a legitimate and necessary foundation for rigorous STEM learning. Keywords: ethnomathematics; ethnopedagogy; STEM education; critical understanding; teacher education.